KETERLAKSANAAN STANDAR PENGELOLAAN PENDIDIKAN DI SMA TERAKREDITASI - Krisma Widi Wardani; Lobby Loekmono; Supramono Supramono (Kelola: Jurnal Manajemen Pendidikan, 2017)
This study aims: (1) to find out the significance of differences in the implementation of the Education Management Standards in Semarang Regency Accredited Senior High School, and (2) to know the implementation of components in the Education Management Standards at Senior High School (SHS) accredited A and B in Semarang Regency which is still in the Very Low category.  The type of this research is descriptive comparative with quantitative approach. The sample in this study consists of 6 Accredited A and 3 Accredited B SHSs. Data or information obtained from the Principals, Vice Principals and Teachers. There are 30 respondents from 6 Accredited A and 15 people from 3 Accredited B Senior High Schools. This study used a Monitoring and Evaluation of Education Management Standards questionnaire developed by BSNP 2012. The results showed that the average in Accredited A are higher from Accredited B SHSs. While from the comparative test results obtained: there is no significant difference in the implementation of education management standards between Accredited A and Accredited B Senior High Schools in Semarang Regency. The result of the categorization statistics is the result that there is no component whose implementation in the Very Low category in both Accredited A and Accredited B Senior High School. However, there are components whose implementation is still in the Moderate category of the Component Management Information System.